Relationship Between Dyslipidemia and Albuminuria in Hypertensive Adults: A Nationwide Population-Based Study. Issue 16 (April 2016) - Lee, Sung-Ho; Kim, Do Hoon; Kim, Yang-Hyun; Roh, Yong Kyun; Ju, Sang Yhun; Nam, Hyo-Yun; Nam, Ga-Eun; Choi, Jun-Seok; Lee, Jong-Eun; Sang, Jung-Eun; Han, Kyungdo; Park, Yong-Gyu
Abstract : Abstract: This study aimed to estimate the relationship between various lipid abnormalities and albuminuria in hypertensive Korean adults. Data obtained from the Korea National Health and Nutrition Examination Survey in 2011 to 2012 were analyzed. The study included 2330 hypertensive participants. Total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels were measured. Dyslipidemia parameters were defined as high TG ≥200 mg/dL, low HDL-C as HDL-C <40 mg/dL, high TC/HDL-C as TC/HDL-C ratio ≥4, high TG/HDL-C as TG/HDL-C ratio ≥3.8, and high LDL-C/HDL-C as LDL-C/HDL-C ratio ≥2.5. Albuminuria was defined as a urine albumin to creatinine ratio (ACR) ≥30 mg/g. Women with albuminuria showed significantly higher levels of TG, TC/HDL-C, and TG/HDL-C and a lower level of HDL-C than women without albuminuria (all P < 0.05). LogTG, TC/HDL-C, and logTG/HDL-C were positively correlated with ACR in both men and women; however, HDL-C was negatively correlated with ACR in women and non-HDL-C was positively correlated with ACR in men. In men, there was no association between ACR and lipid parameters. However, in women, higher values for logTG, TC/HDL-C, and logTG/HDL-C were associated with an increased odds ratio (OR) for albuminuria (OR [95% confidence interval]: 1.53 [1.06–2.21], 1.21 [1.02–1.45], and 1.78 [1.21–2.63], respectively) and HDL-C with a decreased OR for albuminuria (0.78 [0.67–0.92]) after adjusting for all covariates. LogTG, TC/HDL-C, and logTG/HDL-C were associated with an increased prevalence of albuminuria in hypertensive women. Screening and treatment for dyslipidemia may be necessary for hypertensive women to address potential albuminuria.